2020
DOI: 10.1177/0954405420935787
|View full text |Cite
|
Sign up to set email alerts
|

An intelligent prediction model of the tool wear based on machine learning in turning high strength steel

Abstract: In the process of high strength steel turning, tool wear will reduce the surface quality of the workpiece and increase cutting force and cutting temperature. To obtain the fine surface quality and avoid unnecessary loss, it is necessary to monitor the state of tool wear in the dry turning. In this article, the cutting force, vibration signal and surface texture of the machined surface were collected by tool condition monitoring system and signal processing techniques are being used for extracting the time-doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Due to the complexity of tool wear during machining process, the establishment of tool wear mechanism models is more and more challenging, while data-driven methods can learn data-driven models from a large volume of data, and the data-driven model can be equivalent to complex mechanism models within certain range of error, so data-driven method provides a new idea for accurate tool wear prediction. 1318…”
Section: Related Workmentioning
confidence: 99%
“…Due to the complexity of tool wear during machining process, the establishment of tool wear mechanism models is more and more challenging, while data-driven methods can learn data-driven models from a large volume of data, and the data-driven model can be equivalent to complex mechanism models within certain range of error, so data-driven method provides a new idea for accurate tool wear prediction. 1318…”
Section: Related Workmentioning
confidence: 99%
“…Currently, the researches on machine learning for manufacturing mainly have been focused on parameter optimization and shape error compensation. 38,39 These works were mainly based on the principle of neural network. However, based on the usage of empirical risk minimization (ERM) criterion to minimize the sampling errors in the training process, the training result will inevitably lead to the over-fitting problem.…”
Section: Machine Learningmentioning
confidence: 99%
“…From the experimental results, it was observed that better results in terms of cutting force, tool wear, tool-chip contact length, and surface roughness were obtained using artificial intelligence-based optimization compared to PSO and the experimental approach. Cheng et al (2020) predicted the tool wear based on machine learning during the turning of high-strength steel. Two prediction models are used one is grid search algorithm-based support vector and the other is genetic algorithm-based support vector regression.…”
Section: Introductionmentioning
confidence: 99%